A robust method to determine the contact resistance using the van der Pauw set up. (February 2017) - González-Díaz, G.; Pastor, D.; García-Hemme, E.; Montero, D.; García-Hernansanz, R.; Olea, J.; del Prado, A.; San Andrés, E.; Mártil, I.
Abstract: The van der Pauw method to calculate the sheet resistance and the mobility of a semiconductor is a pervasive technique both in the microelectronics industry and in the condensed matter science field. There are hundreds of papers dealing with the influence of the contact size, non-uniformities and other second order effects. In this paper we will develop a simple methodology to evaluate the error produced by finite size contacts, detect the presence of contact resistance, calculate it for each contact, and determine the linear or rectifying behavior of the contact. We will also calculate the errors produced by the use of voltmeters with finite input resistance in relation with the sample sheet resistance.